Workplace sexual harassment in Singapore: The legal challenge - LEE, Jack Tsen-Ta (Institutional Knowledge at Singapore Management University, 1999)
This article examines the nature and prevalence of sexual harassment in the work environment, and compares civil and criminal law in Singapore to the approaches taken by various jurisdictions in dealing with the problem. It is submitted that legislation is needed to protect employees, as Singapore law currently does not present any clear and coherent means for victims to seek redress for workplace sexual harassment.